2022
DOI: 10.1044/2022_aja-22-00073
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency Narrowband Chirp Evoked Cervical Vestibular Myogenic Potentials: Evaluation of Responses in Normal-Hearing Young Adults

Abstract: Purpose: The study aimed to explore the various parameters of multifrequency narrowband Claus Elberling chirp (NB CE-chirp) evoked cervical vestibular evoked myogenic potentials (cVEMPs) in normal-hearing healthy young adults. The study also attempted to define the optimal frequency tuning characteristic of NB CE-chirp evoked cVEMPs. Method: cVEMP was performed on 26 young healthy adults using four different NB CE-chirps centered at 500, 1000, 2000, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Although earlier studies have compared P1N1 amplitudes of the cVEMPs across single or two frequencies, 8,14,15 the present study is the initial one to compare cVEMPs over four octaves as often suggested in the literature. 16,17,18 Though the findings of the present study were consistent with the study by Özgür et al 26 and Ocal et al 8 it rejected the claim by some other studies. 14,15,24 Wang et al 24 published the first report of CE-chirp eliciting a significantly greater amplitude than 500 Hz tone bursts.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 2 more Smart Citations
“…Although earlier studies have compared P1N1 amplitudes of the cVEMPs across single or two frequencies, 8,14,15 the present study is the initial one to compare cVEMPs over four octaves as often suggested in the literature. 16,17,18 Though the findings of the present study were consistent with the study by Özgür et al 26 and Ocal et al 8 it rejected the claim by some other studies. 14,15,24 Wang et al 24 published the first report of CE-chirp eliciting a significantly greater amplitude than 500 Hz tone bursts.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…12,13 In meantime, these chirp stimuli have been effective in eliciting VEMP responses as well. 8,14,15,16 In the study by Ocal et al 8 NB CE-chirps and tone bursts at 500Hz were found to elicit no significant variations in P1N1 amplitude, however, the latency was significantly shortened with NB CE-chirp. On contrary, Reddy et al 15 revealed significantly larger cVEMP amplitude responses for 500 Hz NB CE-chirps than broadband chirps, clicks, and 500Hz tone bursts.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…and cVEMPs (Lodha & Neupane 20 ; Sandhu et al 25 ) elicited using 500 Hz tone bursts. The responses of the otolith organs are known to exhibit greater prominence at lower mechanical resonance frequencies, which may explain present reflexes for all participants (Sandhu et al 25 ;…”
Section: Discussionmentioning
confidence: 99%
“…The electrode montage for cVEMP involved placing an inverting electrode at the sternocleidomastoid muscle, i.e., one-third region of the muscle, a non-inverting electrode at the sternoclavicular junction, and a common ground electrode on the lower forehead as given in Fig. 1 (Lodha & Neupane 20 ). Cervical VEMP was elicited using a 500Hz tone burst with a rise/fall and plateau time of one millisecond.…”
Section: Recording Of Cvempmentioning
confidence: 99%